The theory of planned behavior and dietary behaviors in competitive women bodybuilders - John E. Haubenstricker; Jerry W. Lee; Gina Segovia-Siapco; Ernesto Medina (BMC, 2023)
Abstract Background Women bodybuilders build their ideal physique by manipulating their diet, supplement, and exercise regimens to extreme levels. Excess protein intake and dietary supplement use is ubiquitous in women bodybuilders preparing for a competition, i.e., in-season competitors, however the impetus for these two dietary behaviors are relatively unknown. The Theory of Planned Behavior (TPB) has been used to explain dietary behaviors. The purpose of the study was to examine how the TPB can explain protein intake and dietary supplement use in in-season competitors. Methods Using a cross-sectional design, an online questionnaire was developed, validated, and administered to collect dietary supplement use, TPB variables, and other measures from 112 in-season competitors. Protein intake was assessed using multiple 24-h dietary recalls. Associations between TPB and protein intake and dietary supplement use were determined with multiple regression analysis while adjusting for confounders. Results For protein intake: attitude, subjective norm, and perceived behavioral control explained 8% of the variance in intention; subjective norm independently predicted intention. Behavioral beliefs predicted attitude; subjective norm was predicted by trainer/coach, workout partners, and social media influencers. For dietary supplement use: intention explained 5% of the variance in dietary supplement use; attitude, subjective norm, and perceived behavioral control together explained 38% of the variance in intention. Attitudes towards dietary supplements use were predicted by five factors (not a waste of money, help improve physique, sustain energy levels, provide enough calories, help with recovery). Primary determinants of subjective norm were fellow competitors, social media influencers, and trainer/coach. Perceived behavioral control was predicted by three factors (ease of purchase, affordability to purchase, availability to purchase). Conclusions TPB predicted dietary supplement use in women bodybuilders during in-season but there was little evidence for the prediction of protein intake using the TPB. Health professionals should develop effective interventions using strategies that align health education messages with in-season competitors' outcome beliefs and collaborate with their referent others to influence safer and effective dietary supplement use.